2021
DOI: 10.3390/ijerph18115520
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Differentiated Analysis of the Correlation between Active Commuting to School vs. Active Commuting to Extracurricular Physical Activity Practice during Adolescence

Abstract: Active commuting to school in children and adolescents can help achieve compliance with the World Health Organization (WHO) recommendations for physical activity. This study aimed to evaluate the relationship between the mode of transport used to go to school and the mode of transport used to go to extracurricular sports practice. Multistage random cluster sampling was conducted to include 128 schools with the participation of 11,017 students between the ages of 5 and 19. Participants completed the survey of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
(28 reference statements)
0
4
2
Order By: Relevance
“…Interestingly, our study did not show many gender differences in active commuting to school. A recent study reported that girls are more likely to use motorized transport than boys [48], although we did not find such a difference. However, we found that boys were more likely to use wheeled modes of commuting (e.g., bicycle, skateboard) and girls were more likely to walk.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, our study did not show many gender differences in active commuting to school. A recent study reported that girls are more likely to use motorized transport than boys [48], although we did not find such a difference. However, we found that boys were more likely to use wheeled modes of commuting (e.g., bicycle, skateboard) and girls were more likely to walk.…”
Section: Discussioncontrasting
confidence: 99%
“…From this, we could infer that the preferred activities of older children shifted in favor of more sedentary activities such as the use of mobile phones and screens; at the same time, surgical indications have evolved. Young children (1–5 years) seemed to be more active and may have been more involved in physical activities in 2019 compared with 1999 [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of new leisure devices such as hoverboards, electric scooters, trampolines, and monkey bars has led to changes in the daily activities of the pediatric population with a possible change in traumatic mechanisms. In addition, the physical and extracurricular activities offered to schoolchildren have further evolved with the feminization or masculinization of several sports [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the concept of sustainable sports has been in the spotlight for some time [ 13 ], the methods by which children and adolescents get to practice have not received much attention. The few studies on the topic to date indicate a culture of chauffeuring young athletes to organized sporting activities, contributing to increased congestion during rush hour [ 7 , 15 , 16 , 17 ]. While the reasons for opting for travel by car are multifactorial, previous studies have pointed to time concerns, safety concerns, distance from home to the field of practice, and the built environment as determinants [ 12 , 15 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the reasons for opting for travel by car are multifactorial, previous studies have pointed to time concerns, safety concerns, distance from home to the field of practice, and the built environment as determinants [ 12 , 15 , 18 , 19 ]. Various sociodemographic factors such as age, ethnicity, and socioeconomic status have previously been found to be associated with active travel behavior in other contexts [ 16 , 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%